Cooperation and Metacontingency in Pigeons. - Velasco, Saulo; Benvenuti, Marcelo; Sampaio, Angelo; Tomanari, Gerson (Psychological Record, 2017)
Three pairs of pigeons were exposed to a procedure that combined features of classic studies on social behavior (cooperation) and recent studies that were inspired by the notion of metacontingency. We examined interactions between simultaneous demands for behavior of individual pigeons and interlocked behaviors of pairs of pigeons. The pigeons worked face to face in an operant conditioning box that was divided by a transparent wall. Each side of the box had two horizontally aligned response keys on the floor. Working individually, each pigeon produced 3-s access to food (individual consequence). In a subsequent phase, if the pigeons coordinated their responses, then they could produce food for an additional 4 s (mutual consequence). Initially, the individual consequence was produced on more than 75% of the trials. The interlocking pattern that was required to produce mutual consequences in the subsequent phase was observed on less than 50% of the trials for all pairs of pigeons. Adding the mutual contingency of reinforcement led to (a) a slight reduction of the production of individual and mutual consequences without any coordinated response pattern; (b) the maintenance of high percentages of individual consequences with a concomitant increase in mutual consequences; and (c) for only one subject, an increase in the production of mutual consequences that were accompanied by a decrease in the rate of individual consequences. We discuss the ways in which cooperation and metacontingency experiments should be integrated, the ways in which interlocking behaviors of nonhuman animals can be generated, and the role of verbal behavior in the emergence of cooperation and cultural processes.